2022
DOI: 10.3390/pharmaceutics14112543
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis and Diabetic Foot Ulcer: Role of Probiotics

Abstract: Diabetic foot ulcer (DFU) is a multifactorial disease and one of the complications of diabetes. The global burden of DFU in the health sector is increasing at a tremendous rate due to its cost management related to hospitalization, medical costs and foot amputation. Hence, to manage DFU/DWs, various attempts have been made, including treating wounds systematically/topically using synthetic drugs, herbal drugs, or tissue engineering based surgical dressings. However, less attention has been paid to the intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“… 46 , 47 Obviously, as the most typical complication of T2DM, DFUs characterized by macrovascular and microvascular pathological changes are inevitably related to the core pathological mechanism of insulin resistance. 48 , 49 Our prior research also supported the finding about the fundamental mechanism of insulin resistance in cardiovascular adverse events of DFUs. 50 Given this, MAFLD causes several clinical adverse vascular outcomes in patients with DFUs through the mediation of insulin resistance.…”
Section: Discussionsupporting
confidence: 82%
“… 46 , 47 Obviously, as the most typical complication of T2DM, DFUs characterized by macrovascular and microvascular pathological changes are inevitably related to the core pathological mechanism of insulin resistance. 48 , 49 Our prior research also supported the finding about the fundamental mechanism of insulin resistance in cardiovascular adverse events of DFUs. 50 Given this, MAFLD causes several clinical adverse vascular outcomes in patients with DFUs through the mediation of insulin resistance.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, hospital-acquired and ventilator-associated pneumonia cases that required intensive care have been found to have increased hospitalization time and costs 21 , 22 . The impact of development of DM and infectious complications in DM patients on hospitalization costs has also been frequently reported 23 25 . In other studies, oral bacterial infection and poor oral health were shown to be risk factors related to surgical site infection after various cancer and cardiovascular surgical procedures 9 , 26 – 29 , while a relationship between oral microbial colonization and ventilator-associated pneumonia in patients in intensive care units has also been reported 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] In DFU, LPS is a significant contributor to insulin resistance and inflammation due to immunopathy and the production of oxidative stress, which directly contribute to the development of DFU. [ 24 ] In addition, LPS promotes the release of inflammatory cytokines and chemokines associated with osteomyelitis, which activate NF-κB, upregulating toll-like receptor 3 (TLR3) gene expression, monocyte chemotactic protein 1 (CCL2), matrix metalloproteinase 9 (MMP9). Further, it promotes IL-8, and IL-10 gene expression and secretion.…”
Section: Discussionmentioning
confidence: 99%